SISTER CHROMATID EXCHANGES IN HETEROZYGOTE BETA-THALASSEMIC PATIENTS WITH NORMAL FOLATE LEVELS - Silva, A. E.; Manzato, A. J.; Varellagarcia, M. (Soc Brasil Genetica, 1993)
Lymphocytes from beta thalassaemia heterozygote patients, with normal levels of plasma folic acid cultured for 72 h in a folate rich medium, were not found to contain increased rates of sister chromatid exchanges (SCE). A wide intra and interindividual variability was found in both thalassaemic and control groups and methodological and biological factors, such as types of peripheral lymphocytes, sex, age, and smoking, alcohol and coffee drinking, as well as dietary habits, are possibly responsible for these variations.